Decline of Orientation and Direction Sensitivity in the Aging Population - Xia, Lin; Chen, He; Dong, Jiong; Luo, Sha; Feng, Lixia (Frontiers in Neuroscience, 2021)
While the population of aging is growing, our knowledge about the deterioration of visual perception is still limited. In the present study, we investigated the effects of aging on orientation and direction sensitivity in a healthy population. A weighted up-down adaptive method was used to improve the efficiency and reliability of the task. A total of 57 healthy participants aged 22–72 years were recruited and divided into old and young groups in this study. Raw experimental data were processed using a psychometric method to determine differences between young and old participants. In the orientation task, the threshold of the discrimination angle and bias of the perceived midpoint increased, while the lapsing rate did not change significantly in the old group compared with the young group. In the motion direction task, the threshold, bias and lapsing rate were significantly increased in the old group compared with the young group. These results suggest that in aging people, the function of the visual cortex, especially the neural function of orientation or motion direction discrimination, is partly impaired.